Standardization of Epidemiological Surveillance of Rheumatic Heart Disease . (15th September 2022) - Scheel, Amy; Miller, Kate M; Beaton, Andrea; Katzenellenbogen, Judith; Parks, Tom; Cherian, Thomas; Van Beneden, Chris A; Cannon, Jeffrey W; Moore, Hannah C; Bowen, Asha C; Carapetis, Jonathan R; ,
Abstract: Rheumatic heart disease (RHD) is a long-term sequela of acute rheumatic fever (ARF), which classically begins after an untreated or undertreated infection caused by Streptococcus pyogenes (Strep A). RHD develops after the heart valves are permanently damaged due to ARF. RHD remains a leading cause of morbidity and mortality in young adults in resource-limited and low- and middle-income countries. This article presents case definitions for latent, suspected, and clinical RHD for persons with and without a history of ARF, and details case classifications, including differentiating between definite or borderline according to the 2012 World Heart Federation echocardiographic diagnostic criteria. This article also covers considerations specific to RHD surveillance methodology, including discussions on echocardiographic screening, where and how to conduct active or passive surveillance (eg, early childhood centers/schools, households, primary healthcare), participant eligibility, and the surveillance population. Additional considerations for RHD surveillance, including implications for secondary prophylaxis and follow-up, RHD registers, community engagement, and the negative impact of surveillance, are addressed. Finally, the core elements of case report forms for RHD, monitoring and audit requirements, quality control and assurance, and the ethics of conducting surveillance are discussed. Abstract : This article presents case definitions for clinical rheumatic heart disease and best-practice protocols for conducting epidemiological surveillance for rheumatic heart disease in a variety of settings.